Keberlanjutan Pembangunan Infrastruktur di Indonesia: Analisis Yuridis Penyesuaian Harga dalam Kontrak Konstruksi - Yanuar, Riko; Saputro, Adi; Sami’an, S. (SIGn Jurnal Hukum, 2024)
This study examines the mechanism of price adjustments in construction contracts in Indonesia from philosophical, juridical, and practical perspectives. The background of this issue stems from fluctuations in construction material prices, which often threaten the sustainability of infrastructure projects. To address this issue, this study aims to analyze the philosophical foundations and legal doctrines underlying the price adjustment mechanism, evaluate the regulatory framework in Indonesia, and formulate recommendations to enhance the effectiveness of dispute prevention and resolution mechanisms. Employing a juridical-normative research method, this study analyzes the principle of contractual fairness and the doctrine of rebus sic stantibus as the foundation for price adjustments. The results show that Law Number 2 of 2017, Presidential Regulation Number 16 of 2018, and their implementing regulations have regulated the mechanism of price adjustments; however, their implementation still faces obstacles in the form of administrative complexity and transaction costs. To increase the effectiveness of this mechanism, the standardization of price adjustment clauses referring to international best practices, such as the FIDIC contract standards, is needed. In addition, optimization of a digital technology-based price information system, capacity building for stakeholders, and development of effective dispute resolution mechanisms, mainly through arbitration, are necessary. In conclusion, this study affirms that harmonising philosophical foundations, legal doctrines, adaptive regulations, and effective dispute prevention and resolution mechanisms is the key to optimizing price adjustments in construction contracts to support the investment climate and sustainable infrastructure development in Indonesia.